Effects of absorbed hydrogen on fracture toughness of welded SA516 Grade-70 steel - Mohamad Haidir Maslan, 1981-; Mohd. Nasir Tamin, supervisor; Fakulti Kejuruteraan Mekanikal (2007)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2007